La historia de Ernesto - Company Gonzalez, Merce; Lavarello, Jose M. (Madrid : Ediciones SM, 2008)
Six year old Ernesto and his parents celebrate the anniversary of his "arrival" and Ernesto "adopts" a kitten, occasioning questions from Ernesto and reminiscences by his parents. Ernesto is secure in the knowledge that even though he is not his parents' biological child, he was very much wanted and is very much loved and the three are every bit a real family.
"Premio de Literatur Infantil de la Generalitat de Cataluna 1985."
Translation of: L'historia de l'Ernest.
Keywords: Adoption -- Juvenile fiction; Adopted children -- Juvenile fiction; Adopcion -- Novela juvenil; Spanish language materials